Decoding Melanoma Development and Progression: Identification of Therapeutic Vulnerabilities - Eddy, Kevinn; Shah, Raj; Chen, Suzie (Frontiers in Oncology, 2021)
Melanoma, a cancer of the skin, arises from transformed melanocytes, which are the pigment producing cells of the skin. Melanoma has the highest mutational burden of any cancer partially attributed to UV induced DNA damages. Localized melanoma is “curable”, by surgical resection, followed by radiation therapy to eliminate any remaining cancer cells. Targeted therapies against components of the MAPK signaling cascade and immunotherapies which block immune checkpoints have shown remarkable clinical responses however they are marked by onset of resistance, disease relapse, low response rates, and become refractory to treatments quickly. Although great advances have been made in our understanding of the metastatic process in cancers including melanoma, therapy failure suggests that early stage cancer patients should be given metastatic therapies in the neoadjuvant or adjuvant setting to prevent the spread of localized disease. In this review we provide an overview of melanocytic transformation into malignant melanoma and shed light on the key molecular events that occur during this evolution. A better understanding of the complex processes entailing cancer cell dissemination will improve the mechanistic driven design of combination therapies that target specific steps involved in cancer metastasis, improving clinical response rates and overall survival of patients battling cancer.